Expression and Evaluation of a Novel PPRV Nanoparticle Antigen Based on Ferritin Self-Assembling Technology - Dan Li; Haozhi Song; Jialei Li; Xingjian Liu; Xintao Gao; Tong Wu; Zhifang Zhang; Yinü Li (MDPI AG, 2022)
Peste des Petits Ruminants (PPR) is a highly pathogenic disease that is classified as a World Organization for Animal Health (OIE)-listed disease. PPRV mainly infects small ruminants such as goats and sheep. In view of the global and high pathogenicity of PPRV, in this study, we proposed a novel nanoparticle vaccine strategy based on ferritin (Fe) self-assembly technology. Using Helicobacter pylori (H. pylori) ferritin as an antigen delivery vector, a PPRV hemagglutinin (H) protein was fused with ferritin and then expressed and purified in both Escherichia coli (E. coli) and silkworm baculovirus expression systems. Subsequently, the nanoparticle antigens' expression level, immunogenicity and protective immune response were evaluated. Our results showed that the PPRV hemagglutinin-ferritin (H-Fe) protein was self-assembled in silkworms, while it was difficult to observe the correctly folded nanoparticle in E. coli. Meanwhile, the expression level of the H-Fe protein was higher than that of the H protein alone. Furthermore, the immunogenicity and protective immune response of H-Fe nanoparticle antigens expressed by silkworms were improved compared with the H antigen alone. Particularly, the protective immune response of H-Fe antigens expressed in E. coli did not change, as opposed to the H antigen, which was probably due to the incomplete nanoparticle structure in E. coli. This study indicated that the use of ferritin nanoparticles as antigen delivery carriers could increase the expression of antigen proteins and improve the immunogenicity and immune effect of antigens.